Characteristics associated with drug-induced liver injury from interferon beta in multiple sclerosis patients. (October 2014) - Kowalec, Kaarina; Kingwell, Elaine; Yoshida, Eric M; Marrie, Ruth Ann; Kremenchutzky, Marcelo; Campbell, Trudy L; Wadelius, Mia; Carleton, Bruce; Tremlett, Helen
<x xml:space="preserve">Abstract</x> Objective: To identify and characterize drug-induced liver injury (DILI) associated with IFN-β in multiple sclerosis (MS) using recommended criteria. Methods: This retrospective, mixed methods design included a cohort of IFN-β exposed MS patients from British Columbia (BC), Canada and a series of DILI cases from other Canadian provinces and two adverse drug reaction (ADR) networks (USA and Sweden). Associations between sex, age and IFN-β product, and DILI were explored in BC cohort using Cox proportional hazard analyses. Characteristics, including the time to DILI, were compared between sites. Results: In BC, 18/942 (1.9%) of IFN-β exposed MS patients met criteria for DILI, with a trend toward an increased risk for women and those exposed to IFN-β-1a SC (44 mcg 3 × weekly) (adjusted Hazard Ratios: 3.15;95% CI:0.72 – 13.72, p = 0.13 and 6.26;95%CI:0.78 – 50.39, p = 0.08, respectively). Twenty-four additional cases were identified from other sites; the median time to DILI was comparable between BC and other Canadian cases (105 and 90 days, respectively), but longer for the ADR network cases (590 days, p = 0.006). Conclusions: Approximately 1 in 50 IFN-β exposed patients developed DILI in BC, Canada. Identification of DILI cases from diverse sources highlighted that this reaction occurs even after years of exposure.